2022
DOI: 10.3389/fanim.2022.998042
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of dietary seaweeds and their bioactive compounds in sustainable poultry production systems: A symphony of good things?

Abstract: Modern poultry production systems face numerous economic, environmental, and social sustainability challenges that threaten their viability and acceptability as a major source of animal protein. As scientists and producers scramble to find cost-effective and socially acceptable solutions to these challenges, the dietary use of marine macroalgae (seaweeds) could be an ingenious option. Indeed, the incredible array of nutritive and bioactive compounds present in these macroscopic marine organisms can be exploite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 159 publications
0
0
0
Order By: Relevance
“…Microalgae are sustainable natural bioresources that do not compete with terrestrial plants for arable land, freshwater, pesticides, fertilizers, and insecticides to grow, and yet they have high productivity [169]. Thus, substituting synthetic feed additives with microalgae could result in positive environmental outcomes in the livestock sector with higher-quality nutritional products [170][171][172][173][174].…”
Section: Discussionmentioning
confidence: 99%
“…Microalgae are sustainable natural bioresources that do not compete with terrestrial plants for arable land, freshwater, pesticides, fertilizers, and insecticides to grow, and yet they have high productivity [169]. Thus, substituting synthetic feed additives with microalgae could result in positive environmental outcomes in the livestock sector with higher-quality nutritional products [170][171][172][173][174].…”
Section: Discussionmentioning
confidence: 99%
“…According to a review by Mlambo et al (2022) [50], bioactive compounds have been reported to modulate the immune system, improve nutrient utilization efficiency and growth rates, improve product quality and stability, and prevent disease outbreaks in poultry. At the same time, the rapid growth in demand for seaweed as an alternative to antibacterial and anti-inflammatory drugs of chemical synthesis is due to the use and search for natural bioactive products [51].…”
Section: Morphological Blood Parameters and Immunty Status Of Brown N...mentioning
confidence: 99%
“…Unlike conventional grains, nutraceutical sources such as brown seaweed ( Ecklonia maxima ) have no direct food value for humans and have been largely harvested to produce animal feed, fertilizers, plant bio-stimulants and alginate over the last few years 5 . Thus, their use in Boschveld chicken diets can be a strategy to deliver sustainable chicken production systems in South Africa 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Brown seaweeds are rich sources of bioactive substances such as polyphenols, polysaccharides (alginate, agar, and carrageenan) and polyunsaturated fatty acids, which possess various biological functionalities with antiviral, antibacterial, antifungal, prebiotic, immunomodulatory, anti-inflammatory, and cholesterol-lowering effects 7 , 8 . These biomolecules have the potential to stimulate growth performance, promote immunological responses, and safeguard the chickens against debilitating pathogenic infections 6 , 9 .…”
Section: Introductionmentioning
confidence: 99%